Atmosphere Dynamics E-Module Development Based On Contextual Learning For Geography Learning in High School - Partini, Dwi; Anwar, Yaskinul; Kurniaaji, Bayu; Rahmawati, Arfita (Universitas Veteran Bangun Nusantara, 2022)
ABSTRACT The development of the world is so fast marked by the very rapid progress of science and technology, globalization has an impact on all sectors of life, including education. Globalization poses a challenge to the world of education that in the 21st century, 4C competencies (Communication, Collaboration, Critical thinking, and Creativity) are needed so that students in their lives in the future are able to compete and survive in the midst of global competition. The development of 4C competencies in students can be done with various approaches, one of which in this study is the development of contextual learning-based learning e-modules. Through this module, students are presented with factual knowledge that is close to their environment and life so that they can develop critical and creative thinking skills. Communication and collaboration skills are developed with group discussions to complete the exercises in the module. The module was developed using the ADDIE model, based on expert assessments, the atmospheric dynamics learning e-module got a score of mode 4 which was declared feasible to use. Meanwhile, based on the assessment, students got a mode score of 5 on each aspect of the assessment which means very good. Test the effectiveness of the e-module on students with a pretest-post test only design, the score increased from 56.67 to 84.00, which means that the e-module is effective to use.